Constructing identity and social capital on Facebook: a feminist digital sociology of Bangladeshi women - Safa, Md Nurus; Akter, Tahera; Jahan, Nusrat (Frontiers in Psychology, 2025)
Facebook has become a crucial digital platform for women in Bangladesh, facilitating novel avenues for interaction, support, and identity formation within a patriarchal societal framework. This mixed-methods study examines the role of Facebook activity in the construction of social capital and the development of identity among Bangladeshi women. The study utilizes survey data from 357 women, analyzed by Partial Least Squares Structural Equation Modeling (PLS-SEM), to investigate the relationships between Facebook usage, network size and diversity, bonding and bridging social capital, and self-identity outcomes. The findings indicate that increased Facebook participation is a strong predictor of both network variety (β = 0.72) and size (β = 0.55), which subsequently improve bonding (R2 = 0.61) and bridging (R2 = 0.43) social capital. These network-derived social resources enhance the dynamism of identity creation (R2 = 0.425), particularly among women with varied digital connections. Qualitative insights derived from 15 comprehensive interviews elucidate these findings: Participants characterize Facebook as a dual-faceted platform broadening perspectives and facilitating self-expression, while also limited by monitoring, conservative standards, and calculated self-presentation. The research incorporates Social Capital Theory, Social Identity Theory, and Goffman’s dramaturgical framework to illustrate how digital environments simultaneously replicate and challenge gendered power dynamics. These findings enhance feminist digital sociology and ICT4D literature by elucidating how social media platforms facilitate empowerment, connectivity, and identity for women in the Global South.